2017
DOI: 10.1073/pnas.1704012114
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic ZIP14-mediated zinc transport is required for adaptation to endoplasmic reticulum stress

Abstract: Extensive endoplasmic reticulum (ER) stress damages the liver, causing apoptosis and steatosis despite the activation of the unfolded protein response (UPR). Restriction of zinc from cells can induce ER stress, indicating that zinc is essential to maintain normal ER function. However, a role for zinc during hepatic ER stress is largely unknown despite important roles in metabolic disorders, including obesity and nonalcoholic liver disease. We have explored a role for the metal transporter ZIP14 during pharmaco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 64 publications
(80 reference statements)
0
68
0
Order By: Relevance
“…The authors conclude from this that ZIP14 may have a relevance analogue to that of ZnT8 regarding the diagnosis and treatment of type 2 Dm and NAFLD. Current findings by Kim et al [45] showed the relevance of zinc trafficking and the functional ZIP14 activity for adaptation to endoplasmic reticulum (ER) stress connected to metabolic diseases. According to Zhang [46], zinc restriction in the cells triggers ER stress, which highlights the relevance of zinc for maintaining a normal ER function.…”
Section: Main Textmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors conclude from this that ZIP14 may have a relevance analogue to that of ZnT8 regarding the diagnosis and treatment of type 2 Dm and NAFLD. Current findings by Kim et al [45] showed the relevance of zinc trafficking and the functional ZIP14 activity for adaptation to endoplasmic reticulum (ER) stress connected to metabolic diseases. According to Zhang [46], zinc restriction in the cells triggers ER stress, which highlights the relevance of zinc for maintaining a normal ER function.…”
Section: Main Textmentioning
confidence: 99%
“…Zinc and zinc transporters are involved in the development of ER stress and impairment of the protein synthesis, the unfold protein response (UPR; 45). UPR could be triggered in yeasts and in some mammals by zinc restriction UPR [45,52,53]. In the liver, impaired apoptosis leads to dysregulation of the lipid metabolism, causing hepatic steatosis [54].…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 For example, it has been found that zinc can be released from thapsigargin-and inositol 1,4,5-trisphosphate (IP3)-sensitive ER storage in cortical neurons. 13 In light of this, it is unsurprising that a large number of reports demonstrate that the depletion of zinc transporters and zinc deciency can cause ER stress and upregulate the UPR, [14][15][16][17][18] however, the role of 'free' or 'mobile' zinc in this process is little understood due to the lack of suitable molecular tools to image this subcellular region that exist.…”
Section: Introductionmentioning
confidence: 99%
“…In the event of an acute response to excessive ER stress, the UPR is known to elicit cell death response mediated through IRE1 and PERK (Harding et al, 2003, Novoa et al, 2001. In addition, chronic ER stress characterised by the continual burden on the ER function has surprisingly resulted to an adaptative response by the UPR (Rutkowski et al, 2006, Kim et al, 2017. Contrary to the apoptotic response observed in acute ER stress, adaptation to chronic ER stress is characterised by resistance to apoptosis resulting from differential expression of pro-survival signals and stabilisation of UPR components (Rubio et al, 2011).…”
Section: Introductionmentioning
confidence: 99%